Home page for accesible maths 6 Chapter 6 contents

Style control - access keys in brackets

Font (2 3) - + Letter spacing (4 5) - + Word spacing (6 7) - + Line spacing (8 9) - +

6.9 Example

Example.

Find all solutions to the equation dydx=(y+1)(x-2)\frac{dy}{dx}=(y+1)(x-2).

Solution. We transfer the (y+1)(y+1) to the left hand side and integrate, to obtain:

dyy+1=(x-2)dx{\int\frac{dy}{y+1}=\int(x-2)\,dx}

and hence log|y+1|=x2-2x+c.{\log|y+1|=x^{2}-2x+c.} To get this into the form y=h(x)y=h(x), we exponentiate both sides to get: y+1=ex2-2x+c,y+1={e^{x^{2}-2x+c},} or in other words, y=Aex2-2x-1,y={Ae^{x^{2}-2x}-1,} where A=ecA={e^{c}} is a non-zero constant.

Note that we can’t add an arbitrary constant onto yy to get another solution to the equation.